Autophagy: An Overview of Molecular Mechanisms and Its Therapeutic Implications for Health and Disease - Hourolein Arab; Mohammad Reza Mofid; Mahboube Rahmati; Elahe Gharehkhani; Armin Mokhtariye; Mohammad Shokrzadeh (Journal of Mazandaran University of Medical Sciences)
Autophagy is a fundamental process in eukaryotic cells, essential for maintaining cellular homeostasis and promoting survival. This process involves the formation of a structure known as the autophagosome, which sequesters damaged cellular components such as misfolded proteins and dysfunctional organelles. These components are subsequently transported to lysosomes for degradation. Autophagy allows cells to withstand various stress conditions, including nutrient deprivation, hypoxia, and microbial infections. There are three primary types of autophagy: macroautophagy, microautophagy, and chaperone-mediated autophagy, each characterized by distinct mechanisms and features. The autophagy process is tightly regulated by autophagy-related genes (ATG) and consists of several stages: induction, autophagosome formation, fusion with lysosomes, and cargo degradation. Dysfunctional autophagy has been implicated in the development of various diseases, including cancer, neurodegenerative disorders, metabolic diseases, and bacterial or viral infections. Recent studies have highlighted the dual role of autophagy in cancer: while it can act as a tumor suppressor in early stages, it may also support tumor cell survival in advanced stages. In the nervous system, autophagy helps prevent the accumulation of harmful proteins and supports neuronal function. Additionally, autophagy plays a significant role in combating invasive pathogens, serving as a defensive mechanism against bacteria and viruses. Research indicates that autophagy is a promising target for developing new therapeutic strategies for a wide range of diseases. In-depth investigations into the molecular pathways regulating autophagy, particularly the mTOR and AMPK pathways, offer potential avenues for innovative treatments. This review provides a comprehensive analysis of the mechanisms and functions of autophagy, exploring its association with various human diseases. It presents a novel perspective on the potential clinical applications of autophagy, highlighting its role in the development of therapeutic strategies and deepening our understanding of this essential cellular process.